Transforming schools using project-based deeper learning, performance assessment, and common core standards - Lenz, Bob; Wells, Justin; Kingston, Sally (Jossey-Bass, 2015)
"It's not what students know, but what they do with what they know that is importantSchools are changing in response to this reality, and in Transforming Schools Through Project-Based Deeper Learning, Common Core Standards, and Performance Assessment, Bob Lenz, Justin Wells, and Sally Kingston draw on the example of the Envision Education schools, as well as other leading schools around the country, to show how the concept of deeper learning can meet the need for students who are both college and career ready and engaged in their own education.In this book, the authors explain how project-based learning can blend with Common Core-aligned performance assessment for deeper learning. You'll discover how many schools have successfully made the transition from traditional, teacher-centered learning to project-based, deeper learning and find many practical ideas for implementation. Companion DVD and website include videos showing how to implement deeper learning strategies in the classroom Evidence-based descriptions show why deeper learning is right for students Performance assessment experts explain how to align assessments with Common Core by shifting the emphasis from knowing to doing Extensive game plan section provides step-by-step guidance for change Schools are complex organizations, and transformation involves all of the stakeholders, from students to superintendents. But as this book shows, there are amazing benefits to be realized when everyone commits to diving deeper into learning"--Provided by publisher.